PENGARUH EFFECTIVE MIKROORGANISME (EM4) PADA BOKASI DAN WAKTU APLIKASI BOKASI TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SELADA (Lactuca sativa) - Widya Lestari (JURNAL AGROPLASMA, 2019)
This study aims to determine the effect of microorganisms and the application of fertilizer to the growth of lettuce basil (Lactuca sativum). This research was conducted at Damuli Labuhanbatu Regency at ± 50 m altitude. This research uses a complete randomized design of factorial group. The first factor was the effect of microorganism with four treatments ie E1 = 0.5 ml / Kg of fertilizer bokasi, E2 = 1 ml / kg fertilizer bokasi, E3 = 1.5 ml / kg fertilizer bokasi and E4 = 2 ml / kg fertilizer bokasi. The second factor is the time of application of soil fertilizer ie T0 = 1 week before planting, T1 = planting, T2 = 1 week after planting. The parameters observed were plant height, number of leaves and production per sample. The results showed that the treatment of microorganisms was significantly different from plant height, leaf number and production per sample. The treatment time of planting was significantly different to plant height and production per sample and the combination of microorganism treatment and planting time was significantly different to production per sample. Keywords: fertilizer bokasi, lettuce, EM4